2012
DOI: 10.1080/13803395.2012.672966
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of cognitive subtest impairment in the Montreal Cognitive Assessment (MoCA) in a research cohort with normal Mini-Mental State Examination (MMSE) scores

Abstract: The comparative ability of the Montreal Cognitive Assessment (MoCA) and MMSE to detect mild cognitive difficulties was investigated in 107 older adults. The sensitivity of the MoCA to detect cognitive impairment with a cutoff score of <26 was investigated, as compared to the MMSE across all scores, and at a cutoff of ≥27. Performance on MoCA subtests was compared at these MMSE cutoffs to determine profiles of early cognitive difficulties. The MoCA detected cognitive impairment not detected by the MMSE in a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
60
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 23 publications
4
60
1
4
Order By: Relevance
“…39,40 O foco no declínio ligeiro exige a utilização de instrumentos de rastreio sensíveis e, neste novo enquadramento, são apontadas limitações ao MMSE: uma reduzida complexidade das tarefas de memória/ linguagem conduzindo a uma relativa insensibilidade para o DCL e a ocorrência de falsos negativos nos indivíduos com escolaridade elevada; a ausência de tarefas para a avaliação das funções executivas, o que compromete a sua sensibilidade na identificação de patologias frequentes, como a DFT ou DV. 16,[41][42][43][44][45] Paradoxalmente, estudos longitudinais de DCL/ DA-prodrómica demonstram que o MMSE contribui para prever o declínio progressivo e a evolução para demência quando associado a marcadores biológicos como a ressonância magnética 46 ou os biomarcadores do LCR. 47 Além disso, este instrumento continua a ser utilizado como crité-rio praticamente universal de gravidade ou estadiamento, para inclusão de doentes em ensaios clínicos.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…39,40 O foco no declínio ligeiro exige a utilização de instrumentos de rastreio sensíveis e, neste novo enquadramento, são apontadas limitações ao MMSE: uma reduzida complexidade das tarefas de memória/ linguagem conduzindo a uma relativa insensibilidade para o DCL e a ocorrência de falsos negativos nos indivíduos com escolaridade elevada; a ausência de tarefas para a avaliação das funções executivas, o que compromete a sua sensibilidade na identificação de patologias frequentes, como a DFT ou DV. 16,[41][42][43][44][45] Paradoxalmente, estudos longitudinais de DCL/ DA-prodrómica demonstram que o MMSE contribui para prever o declínio progressivo e a evolução para demência quando associado a marcadores biológicos como a ressonância magnética 46 ou os biomarcadores do LCR. 47 Além disso, este instrumento continua a ser utilizado como crité-rio praticamente universal de gravidade ou estadiamento, para inclusão de doentes em ensaios clínicos.…”
Section: Discussionunclassified
“…16,[41][42][43][44][45] Definimos também como objetivo testar a acuidade diagnóstica das pontuações de corte propostas no estudo de validação para o DCL e para as formas mais prevalentes de demência. Comparando os resultados atuais de sensibilidade e de especificidade (referidos na Tabela 3), com os originalmente encontrados (Anexo 2 -http://www.…”
Section: Discussionunclassified
“…More recently, the Montreal Cognitive Assessment (MoCA) 9 has also become increasingly used by clinicians due to its high specificity for detecting cognitive impairment as well as sensitivity to detecting early cognitive changes associated with the development of AD, such as mild cognitive impairment (MCI). 3,[10][11][12] Each of these instruments can be used to establish the presence of dementia as well as the degree of impairment, although clinicians' use of these scales has been shown to vary widely. 13 This article seeks to build upon and update the work of Solomon and colleagues who reported on the correlations between 5 commonly used measures of mental status/functional ability in patients with AD and provided equations to quickly convert scores on any one of these instruments to any other.…”
Section: Introductionmentioning
confidence: 99%
“…According to Parente Considering MoCA test, data from this survey showed that the majority of their items can differentiate the three diagnostic groups. MoCA was developed as an assessment tool for MCI diagnostic and mild cases of dementia [17,20,22,23]. When compared to the MMSE (one of the most widely used screening instruments worldwide) MoCA has more memory items in the assessment, and includes aspects of executive function and a more structured language subitem [7,20].…”
Section: Discussionmentioning
confidence: 99%
“…for at least two weeks, reported by the patient or informant; c) this decline must be present in neuropsychological; and d) should not be met criteria for another disorder or dementia [17,18].…”
Section: Introductionmentioning
confidence: 99%